Leader member exchange and nurse performance: The mediating effect of positive psychological capital - Yuki Fitria; Chiqi Citra Miranti (Jurnal Kajian Manajemen dan Wirausaha, 2022)
This study examines the relationship between leader member exchange (LMX), positive psychological capital (PsyCap) and nurse performance. In this study, the authors also tested the mediating role of positive psychological capital (PsyCap) on the effect of leader-member exchange (LMX) on nurse performance. The authors collected data through questionnaire on 188 contract nurses at RSUP Dr M Djamil Padang to investigate the hypothesized relationship. The results suggest that PsyCap positively and significantly mediates the effect of LMX on nurse performance. In addition, the results also show that the effect of LMX and PsyCap on nurse performance is positive and significant, then the effect of LMX and nurse performance is positive and significant, and finally the effect of Psycap and nurse performance is also positive and significant.